2022
DOI: 10.1111/raq.12666
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of production performance of aquaculture species fed dietary insect meals

Abstract: The present work employed a systematic review and meta‐analysis to quantify the overall effects of various types of insect meal on special growth rate (SGR), feed conversion ratio (FCR) and protein efficiency ratio (PER) of aquatic animals. A total of 107 studies published from 1990 to 2021, targeting 23 freshwater and 17 marine fish species, employing 17 insect species as a replacement for fishmeal, was compiled. Overall, a significantly higher Hedges’ g value for SGR and lower FCR was found in aquatic animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 127 publications
1
34
0
Order By: Relevance
“…When using four edible insects, namely the house cricket (Acheta domesticus L.), the Taiwan giant cricket (Brachytrupes portentosus Serville), the two-spotted cricket (Gryllus bimaculatus De Geer) and the silkworm (Bombyx mori L.), as substitutes for the 25% of SBM in a 60:40 F:C diet, Ahmed et al (2021) found no adverse effects on rumen fermentation characteristics or nutrient digestibility. This clearly suggests, as expected and recently confirmed by Phesatcha et al (2022), that the insect dietary inclusion level also significantly affects fermentation and digestibility, as already reported to occur for monogastric animals (Elahi et al, 2022;Hong and Kim, 2022;Tran et al, 2022). Furthermore, Phesatcha et al (2022) demonstrated that, when using G. bimaculatus meal as a protein replacement for SBM, regardless of the insect dietary inclusion or substitution level, fermentation and digestibility parameters were also affected by the F:C ratio of the diet, thus highlighting the great complexity of factors and interactions involved.…”
Section: Digestibility and Methanogenesissupporting
confidence: 87%
“…When using four edible insects, namely the house cricket (Acheta domesticus L.), the Taiwan giant cricket (Brachytrupes portentosus Serville), the two-spotted cricket (Gryllus bimaculatus De Geer) and the silkworm (Bombyx mori L.), as substitutes for the 25% of SBM in a 60:40 F:C diet, Ahmed et al (2021) found no adverse effects on rumen fermentation characteristics or nutrient digestibility. This clearly suggests, as expected and recently confirmed by Phesatcha et al (2022), that the insect dietary inclusion level also significantly affects fermentation and digestibility, as already reported to occur for monogastric animals (Elahi et al, 2022;Hong and Kim, 2022;Tran et al, 2022). Furthermore, Phesatcha et al (2022) demonstrated that, when using G. bimaculatus meal as a protein replacement for SBM, regardless of the insect dietary inclusion or substitution level, fermentation and digestibility parameters were also affected by the F:C ratio of the diet, thus highlighting the great complexity of factors and interactions involved.…”
Section: Digestibility and Methanogenesissupporting
confidence: 87%
“…Nairuti et al (2021) reviewed several studies for possible replacement levels of fishmeal with black soldier fly meal and this ranged from 10% for meager juveniles (Argyrosomus regius) to 25% for Siberian sturgeon (Acipenser baerii) and pacific white shrimp (Litopenaeus vannamei), 50% for European sea bass (Dicentrarchus labrax) to 100% for Nile tilapia (Oreochromis niloticus). Tran et (2022) reviewed 107 studies dealing with 23 freshwater and 17 marine fish species, and 17 insect species as a replacement for fishmeal. Two insect meal forms were superior, namely larval defatted Tenebrio molitor and pupal full-fat Bombyx mori, over others in terms of production performance indices.…”
Section: Aquafeedmentioning
confidence: 99%
“…Tran et al . (2022) reviewed 107 studies dealing with 23 freshwater and 17 marine fish species, and 17 insect species as a replacement for fishmeal. Two insect meal forms were superior, namely larval defatted Tenebrio molitor and pupal full‐ fat Bombyx mori , over others in terms of production performance indices.…”
Section: Insects Used For Feedmentioning
confidence: 99%
“…The utilization of insect meal for fishmeal and plant protein replacement in aquaculture has been recently addressed by many researchers. Insects represent a sustainable ingredient with a very interesting nutritional profile and, since their production can be based on substrates that comply with the principles of circular economy (e.g., food wastes), they have become one of the main focuses in fish nutrition over the last five years (see reviews [19][20][21][22][23][24][25] for further information on this subject). Indeed, insects are considered an appropriate protein source, with the black soldier fly (Hermetia illucens) and yellow mealworm (Tenebrio molitor) as the most important candidate species.…”
Section: Introductionmentioning
confidence: 99%